Hubungan Komunikasi Terapeutik Bidan Dengan Tingkat Kecemasan Ibu Hamil Trimester Ii Dan Iii Di Wilayah Kerja Puskesmas L. Sidoharjo - Sholehatun Nisa, Yati; Sulastri, Mepi; Rossita, Taufianie (Jurnal Pakar Kesehatan, 2025)
One of the events that can trigger anxiety is pregnancy and childbirth. Some developing countries in the world have a high risk of psychological disorders in pregnant women 15.6% and postpartum women 19.8% including Ethiopia, Nigeria, Senegal, South Africa, Uganda and Zimbabwe (WHO, 2020). The purpose of this study was to determine the relationship between therapeutic communication of midwives with anxiety of pregnant women TM II and III in the Working Area of Puskesmas L Sidoherjo. this study used an analytical survey with a cross sectional approach. Sampling technique by using accidental sampling with 30 respondents. The result of univariate test analysis that almost most of respondents therapeutic communication of midwife in good category which amounted to 20 people, and some of respondents who experienced anxiety which amounted to 17 people. The results of bivariate analysis there is a relationship between therapeutic communication with anxiety in pregnant women where the p value is 0.000 <0.05. The results of this study will add to the reference, and prove whether or not there is a relationship between therapeutic communication with the anxiety level of pregnant women TM II and III in the working area of Puskesmas L.Sidorejo.